Politics, ontology and knowledge in Spinoza - Matheron, Alexandre (Spinoza studies., 2020)
"Alexandre Matheron is considered one of the most important interpreters of Spinoza's philosophy in the 20th century. These 20 essays, translated into English for the first time, focus on ontology, knowledge, politics and ethics in Spinoza, his predecessors and his contemporaries."--Publisher description